Synthesis and Swelling Behavior of Super‐Absorbent Soluble Starch‐g‐poly(AM‐co‐NaAMC14S) Through Graft Copolymerization and Hydrolysis. (14th February 2019) - Lan, Guihong; Zhang, Ming; Liu, Yongqiang; Qiu, Haiyan; Xue, Songsong; Zhang, Tailiang; Xu, Qianxia
Abstract : By introducing sodium 2‐acrylamido‐tetradecanesulfonate (NaAMC14 S) to graft copolymerization of soluble starch and acrylamide (AM), a novel super absorbent resin (SAR) of soluble starch‐ g ‐poly(AM‐ co ‐NaAMC14 S) (SR‐14) is synthesized. Polymer gels are hydrolyzed with sodium hydroxide (NaOH) to convert the function group −CONH2 to −COO ‐ . The structures and qualitative changes of the polymer gels are characterized through Fourier transform infrared spectroscopy (FT‐IR), scanning electron microscopy (SEM), elemental analysis, and rheometer. Results show the polymer gels through the hydrolysis by NaOH increased the water absorbency of the final SR‐14 resin from 31.71 to 1183.43 g g −1 as the degree of hydrolysis (DH) increased from 0 to 80%. Drastic increases in the storage and loss modulus of SR‐14 reflected the intensive molecular structural changes induced by the addition of NaAMC14 S. The changes in the molecular structures of SR‐14 can be attributed to hydrophobic associations among long‐chain alkane. Soluble starch‐ g ‐poly(AM‐ co ‐NaAMC14 S) exhibits the maximum water absorbency of 2536.77 g g −1 in distilled water and 92.98 g g −1 in 0.9 wt.% NaCl solution. In the absence of NaAMC14 S, however, the water absorbency of soluble starch‐ g ‐poly(AM) decreases to 1222.27 g g −1 in distilled water and to 62.29 g g −1 in 0.9 wt.% NaCl solution. Results indicate that NaAMC14 S has potential applications as a material that can enhance the water absorbency of SAR. Abstract : A hydrophobic monomer, sodium 2‐acrylamido‐tetradecanesulfonate (NaAMC14 S), is introduced to enhance the water absorbency of traditional super absorbent resin (SAR) of soluble starch and acrylamide (AM) system. Hydrolysis is a crucial step to convert −CONH2 to −COO ‐, which can increase the amount of hydrophilic groups. The results confirm the initial hypothesis, and synthesized soluble starch‐ g ‐poly(AM‐ co ‐NaAMC14 S) has excellent water absorbency in distilled water and 0.9 wt.% NaCl solution, comparing to traditional soluble starch‐ g ‐poly(AM).